Preparation and performance of alumina ceramic coating doped with aluminum nitride by micro arc oxidation. Issue 10 (July 2020) - Yang, Wei; Wu, Shangkun; Xu, Dapeng; Gao, Wei; Yao, Yuhong; Guo, Qiaoqin; Chen, Jian
Abstract: The present work is focused on the preparation and performance of micro arc oxidation (MAO) ceramic coating doped with aluminium nitride (AlN) on 6061 Al alloy. The results reveal that AlN-doped ceramic coatings could be prepared by plasma discharge with AlN powder or urea added into the electrolyte. Although AlN-doped MAO ceramic coatings present more distinct porous features than those without AlN, they achieved excellent thermal conductivity and insulation performance due to the physical properties of AlN. Compared with the uncoated Al substrate, MAO coatings with or without AlN doping all exhibited an improved wear resistance. AlN-doped MAO coating could considerably inhibit the formation of a transfer layer. This alumina ceramic coating doped with AlN is anticipated to be applied in the field of light-emitting diode (LED) aluminum substrate.